Dietary approaches for patients with heart failure and diabetes. (20th August 2018) - Butler, Thomas; Georgousopoulou, Ekavi N; Mellor, Duane
Abstract: Nutritional management has a key role to play in the management of diabetes and heart failure (HF). There is currently little evidence to make dietary recommendations specifically for people living with both diabetes and HF. Therefore, most nutritional management recommendations for HF and diabetes need to be based on those for people living with diabetes. This review paper details what is known about the nutritional management recommendations for people living with both diabetes and HF. The only specific approach focusing on managing HF which is currently part of nutritional recommendations are those focused upon fluid and sodium intake to reduce blood volume. There is an emerging body of evidence to suggest individuals living with both diabetes and HF could benefit from dietary pattern approaches, e.g. the Mediterranean diet. A range of dietary approaches have been shown to be effective; the key is for nutritional and dietary advice to be carefully tailored to the individual's social situation and food preferences as well as being supportive of the overall medical management of their condition. Copyright © 2018 John Wiley & Sons.